Implementation of the water framework directive 2000/60/EC in the Tevere river basin - Ruisi M. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The Tevere river basin was identified as one of the pilot river basins involved in the testing activity for the implementation of the WFD 2000/60/EC. The experience gained until now allows us to identify characteristic aspects of the WFD in river basins characterized by scarce precipitations during the summer months, such as the Mediterranean river basins. In particular the correct management of groundwater is of vital importance for the achievement of good ecological status, as required by the WFD. This paper illustrates the general approach to water resource planning carried out on a river basin scale, taking into account of hydrogeological river basins.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)